Instrumentos de política ambiental: uma abordagem para sua integração na gestão ambiental empresarial no Brasil - Azevedo, Luís Peres (2009)
This work analyzes the Environmental Political instruments, coosing off, Environmental Impact Studies, Enviromental Licensing and their use in busines management in Brazil. The viability of industrial undertakings in the country – here privileged the energy sector, specifically the nuclear field – by means of environmental legislation, it is processed trough Brazilians Environmental impact Studies until the granting of licensing, in orderthat such enterprises may begin to operate. Analysis was produced under the oversight of public policies, supported by a surge of neo-institutionalism enhanced with the help of other theoretical sources in order to explain its political character, involving power decisions, through which institutional changes can be filtered. As such a new boarding process utilizing the referenced instruments is proposed, in order that they may be incorporated in environmental business administration. The research is qualitative covering literature review, research and document analysis, choosing a Brazilian large company. Eletrobrás Thermonuclear S.A ( Eletronuclear )as an empirical basis for the study. Other social and institutional actors become involved, who influence in the formulation, adjustment, implementation, monitoring and control of environmental policy in the country are taken into account. The proposed boarding process in this work, takes into consideration the technical, political and institutional elements relating to the use of instruments with fundamental importance, since these elements may ( or may not ) enable the creation of conditions for the incorporation of the proposed changes of public environmental policies into the environmental management at company level.